2010
DOI: 10.1063/1.3443578
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear acoustic resonances to probe a threaded interface

Abstract: We evaluate the sensitivity of multimodal nonlinear resonance spectroscopy to torque changes in a threaded interface. Our system is comprised of a bolt progressively tightened in an aluminum plate. Different modes of the system are studied in the range 1-25 kHz, which correspond primarily to bending modes of the plate. Nonlinear parameters expressing the importance of resonance frequency and damping variations are extracted and compared to linear ones. The influence of each mode shape on the sensitivity of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…3,6 A nonlinear resonant method, 6 performed on a model made of two weakly damped materials, confirmed the greater sensitivity of the nonlinear response to the contact quality and demonstrated that a broad frequency band is useful to increase the sensitivity range. A more realistic interface composed of a dental implant and a bone phantom was then studied.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…3,6 A nonlinear resonant method, 6 performed on a model made of two weakly damped materials, confirmed the greater sensitivity of the nonlinear response to the contact quality and demonstrated that a broad frequency band is useful to increase the sensitivity range. A more realistic interface composed of a dental implant and a bone phantom was then studied.…”
mentioning
confidence: 86%
“…This large frequency band is selected to maximize the stability range monitoring. 6 This specific range is also chosen because it contains various modes of the implant. 3 The first nonlinear ultrasonic method used is the scaling subtraction method (SSM).…”
mentioning
confidence: 99%
“…In such study, the nonlinear behavior of the material under inspection was reduced upon increasing torque onto the clamped end. Similar conclusions were drawn by Rivière and coworkers (Rivière et al, 2010). In general, resonant frequency tests aiming…”
Section: -11supporting
confidence: 74%
“…This phenomenon may explain the abrupt transition observed around 20-23 N Á cm. In a previous study, 19 a metal screw was tightened in an aluminum tapped plate (205 and 75 GPa for Young's moduli of steel and aluminium, respectively, 36 giving a 2.7 ratio), and extracted elastic parameters showed only smooth transition over a large torque range. No plastic deformation between these two similar materials was induced in this case.…”
Section: Comparison Of Both Modelsmentioning
confidence: 99%
“…17 Such nonlinearity likely comes from frictional effects and=or clapping sources at an interface, such as micro-cracks or disbonds typically, providing information on the contact integrity and complementing linear elasticity measurements. 18,19 To our knowledge, three groups have attempted measurement of nonlinear parameters at an interface bone=hip prosthesis (bone mock model, 20 in vitro 21 or in vivo). 9,22 In these studies, the system is driven at a single frequency f and harmonics are detected at 2f and 3f if the prosthesis is loose.…”
Section: Introductionmentioning
confidence: 99%